Upaya Peningkatan Omset Hasil Produk PKK Kelurahan Kauman Melalui Pembuatan Logo - Ari Widian Agustina; Arief Bachtiar; Kiki Asmara (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Family Welfare Empowerment (PKK) is an organization that is oriented towards community empowerment, especially the welfare of housewives. PKK members in the Kauman Village consist of 19 people led by Mrs. Ratna. PKK has several activities including catering and trade. During its activities, the PKK sparked a new idea to make a product as a result of empowering the potential of its members, namely Es Cendol Suji with a weekly turnover of Rp 350.000,-. However, the product does not have a strong identity to be able to compete in the market. From this problem, the author took the initiative to help PKK by providing assistance regarding branding through making a logo as a business identity. The purpose of this activity is to give a new identity to the Es Cendol Suji product which is expected to increase PKK income turnover so as to create prosperity for all PKK members.